Revision of Holarctic Teleiodini (Lepidoptera: Gelechiidae) - Lee, Sangmi; Brown, Richard L. (Zootaxa, 2008)
The 25 genera of Teleiodini (Lepidoptera: Gelechiidae) occurring in the Holarctic Region are revised. A new genus and new species, Arcutelphusa talladega, are described from Alabama and Mississippi, United States. Evippe Chambers (1873a) is synonymized with Agnippe Chambers (1872a), Hapalosaris Meyrick (1917) is synonymized with Coleotechnites Chambers (1880b), and Laris Omelko (1988) is synonymized with Parastenolechia Kanazawa (1985). Telphusa is restricted to three species, and Teleiodes is restricted to four species. A key to genera and a checklist of species, which includes 28 new combinations, are provided. Each generic treatment includes descriptions of imagos, including venation and genitalia, and immature stages so far as known, larval hosts, diversity and distribution, and illustrations of selected species.